2018
DOI: 10.3390/ijerph15112331
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cadmium on Degraded Soils Amended with Maize-Stalk-Derived Biochar

Abstract: Biochar has been extensively proven to distinctively enhance the sorption capacity of both heavy metal and organic pollutants and reduce the related environmental risks. Soil pollution and degradation widely coexist, and the effect of biochar addition on adsorption behavior by degraded soils is not well understood. Four degraded soils with different degrees of degradation were amended with maize-stalk-derived biochar to investigate the adsorption of cadmium using batch methods. The maximum adsorption capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Su et al reported that higher soil moisture and OM contents favoring biodegradation in soil and improving microbial activity and soil adsorption [25,26]. Previous studies have shown that if the vegetation litter is reduced, soil OM cannot be replenished [27]. At the same time, wind erosion and freeze-thaw action continuously accelerate the mineralization of soil OM, which will greatly reduce soil fertility [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Su et al reported that higher soil moisture and OM contents favoring biodegradation in soil and improving microbial activity and soil adsorption [25,26]. Previous studies have shown that if the vegetation litter is reduced, soil OM cannot be replenished [27]. At the same time, wind erosion and freeze-thaw action continuously accelerate the mineralization of soil OM, which will greatly reduce soil fertility [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, pollution varies with the change of the spatial position, and the pollution of the soil determined through statistical analyses of solely the sampling points cannot reflect the spatial distribution characteristics of the whole study area [43]. The environmental risk of pollutants is influenced by their absorption behaviour [44].…”
Section: Discussionmentioning
confidence: 99%
“…Biochar, a carbon-rich material, has been successfully used for carbon sink, climate change mitigation and soil remediation [ 3 , 4 , 5 ]. In recent years, biochar has been successfully used to remove heavy metal from wastewater, including Cd [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%